Guided Imagery Management to Overcome Anxiety Among Cadres During The Covid-19 Pandemic - Hana Nafiah; Dyah Putri Aryati (Prosiding University Research Colloquium, 2022)
The Covid-19 pandemic has the potential to create fear, stress, and anxiety among the community and health workers, one of which is cadres as the right hand of basic level services. The public's response during to the pandemic is they feel tension, anxiety, and panic as well as other psychosomatic symptoms. Guided imagery is a distraction technique that can be used to reduce psychological problems such as stress and anxiety. The purpose of this community service activity is to practice guidance imagery management in an effort to overcome the anxiety of cadres during the Covid-19 pandemic. The target in this activity is 24 health cadres in Bugangan Village and carried out on September 26, 2021. The methods used Health Education about anxiety and guidance imagery, measurement of anxiety with the Hamilton Rating Scale for Anxiety (HARS) before practice the guidance imagery, given training guided imagery and then measure anxiety after practice guided imagery. The result showed that mostly moderate anxiety as many as 12 people (50%) before guided imagery and mostly was mild anxiety as many as 13 people (55%) after guided imagery. It can be concluded that the anxiety of cadres after guided imagery has decreased. As a cadre, it is necessary to apply and motivate the surrounding community to be able to train guide imagery in overcoming psychological problems, especially anxiety during the Covid-19 pandemic.